A Chromosome-Level Genome Assembly of the Pygmy Mole Cricket Xya riparia. (6th January 2022) - Feng, Xiaolei; Yang, Nan; Wang, Qilu; Yuan, Hao; Li, Xuejuan; Majid, Muhammad; Zhang, Xue; Cao, Chengquan; Huang, Yuan
Abstract: The pygmy mole cricket Xya riparia (Orthoptera: Tridactyloidea) is rarely studied or widely known. Some species of pygmy mole crickets, however, not only have a potential ecological value but are also important in the study of the evolution of the orthopteran genome and its phylogenetic relationships. The genome resources of pygmy crickets are limited and there are currently no publications referencing this species' genome. In this study, we assembled a reference genome of X. riparia at the chromosomal level using nanopore sequencing and Hi-C technology. An X. riparia genome of 1.67 Gb was successfully assembled from 164.01 Gb of nanopore sequencing data. The genome assembly showed a completeness of 98.97% benchmarking universal single-copy orthologs with a contig N50 of 4.18 Mb and the longest contig being 18.84 Mb. The contigs were clustered, ordered, and correctly oriented on six pseuchromosomes, which covered 95.63% of the genome assembly through Hi-C data with a scaffold N50 of 319.1 Mb and the longest scaffold being 397.8 Mb. Repeat sequences accounted for 42.88% of the whole-genome assembly. A total of 60, 847 noncoding RNAs were detected. Moreover, 16, 468 (87.91%) of the genes were functionally annotated. As this is the first high-quality reference genome of X. riparia at the chromosomal level, it will undoubtedly serve as a valuable resource for ecological, biological, and genetic research on pygmy mole crickets as well as for general research on Orthoptera's genome evolution and phylogenetic relationships.